2019
DOI: 10.1126/sciimmunol.aax7006
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils restrain allergic airway inflammation by limiting ILC2 function and monocyte–dendritic cell antigen presentation

Abstract: Neutrophil mobilization, recruitment, and clearance must be tightly regulated as overexuberant neutrophilic inflammation is implicated in the pathology of chronic diseases, including asthma. Efforts to target neutrophils therapeutically have failed to consider their pleiotropic functions and the implications of disrupting fundamental regulatory pathways that govern their turnover during homeostasis and inflammation. Using the house dust mite (HDM) model of allergic airway disease, we demonstrate that neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 67 publications
4
57
1
Order By: Relevance
“…Although our central question pertaining to the response of PBMCs to poly I:C, a synthetic IFN trigger 18 and consequently focused on antiviral pathways, we found cell-specific heterogeneity in antigen presentation, phagocytosis, and unfolded protein response in cells of severe asthmatics. Antigen presentation in asthma has multiple implications in disease pathogenesis and intercellular communication [50][51][52] , while the unfolded protein response is dysregulated in asthma and airway inflammation 53,54 . Thus, cell-specific changes in antigen presentation and unfolded protein response pathways may underlie disease heterogeneity in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Although our central question pertaining to the response of PBMCs to poly I:C, a synthetic IFN trigger 18 and consequently focused on antiviral pathways, we found cell-specific heterogeneity in antigen presentation, phagocytosis, and unfolded protein response in cells of severe asthmatics. Antigen presentation in asthma has multiple implications in disease pathogenesis and intercellular communication [50][51][52] , while the unfolded protein response is dysregulated in asthma and airway inflammation 53,54 . Thus, cell-specific changes in antigen presentation and unfolded protein response pathways may underlie disease heterogeneity in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…39 Interestingly, Patel et al recently demonstrated that the regulatory role of neutrophils on ILC2s may rationally account for the failure of neutrophil-targeting therapies for people with asthma. 40 In a mouse model of house-dust-mite-mediated allergic airway inflammation, they found that depletion of neutrophils resulted in a dramatic increase in systemic granulocyte colony-stimulating factor (G-CSF) concentrations, which are ordinarily negatively controlled in the periphery by transmigrated lung neutrophils. G-CSF then functioned to augment allergen sensitization either by activating ILC2s or acting on bone marrow progenitors to drive monocytosis and finally caused the exacerbated Th2 inflammation, epithelial remodeling and airway resistance.…”
Section: Polymorphonuclear Leukocytes and Ilc2smentioning
confidence: 99%
“…G-CSF then functioned to augment allergen sensitization either by activating ILC2s or acting on bone marrow progenitors to drive monocytosis and finally caused the exacerbated Th2 inflammation, epithelial remodeling and airway resistance. 40 Intriguingly, a subpopulation of Lin -GATA3 + ST2 + ILC2s, in the presence of IL-33 and leukotrienes, was found to produce IL-17 in vitro and in a mouse of model of IL-33 or papaininduced lung inflammation, 41 which suggests that some ILC2s may promote the migration of neutrophils to the lung by producing IL-17. Moreover, a recent study showed that short-chain fatty acids derived from fermentation of dietary fibers by the gut microbiota modulated pulmonary ILC2s to secrete IL-17A, which is linked to enhanced neutrophil recruitment to the lung.…”
Section: Polymorphonuclear Leukocytes and Ilc2smentioning
confidence: 99%
“…As a result, we now recognise neutrophils as able to influence and shape adaptive immunity in tissues and in lymph nodes, in both suppressive and activatory manners (reviewed in [18,19]). For example, neutrophils restrain Th2 inflammation during asthma [20], suppress dendritic cell (DC) migration to lymph nodes [21], suppress T cell proliferation in sepsis via Mac-1 [22], and limit humoral responses in lymph nodes [23]. In contrast, they can also directly present antigen to T cells via MHC class II [24], cross-present to CD8 + T cells [25], directly stimulate T cell proliferation in response to superantigen [26], promote type 2 responses in the lung [27], increase DC maturation and co-stimulatory molecule expression [16,[28][29][30] and promote T cell function during influenza infection [31,32].…”
Section: Introductionmentioning
confidence: 99%